Whole-genome sequencing of three local rice varieties (Oryza sativa L.) in Vietnam - Huynh, Ky; Quoc, Giang Van; Thanh, Tung Nguyen Chau; Loc, Hien Nguyen; Thanh, Vo Cong (Plant Science Today, 2021)
Recently, a new technology, Next-generation sequencing (NGS) has been launched and providing whole-genome sequences that helps identify molecular markers across the genome. DNA markers such as single nucleotides and insertion – deletion (InDel) polymorphisms were widely used for plant breeding particularly to distinguish important traits in rice. These PCR-based markers can be used for the precision detection of polymorphisms. Moreover, PCR-based approaches are simple and effective methods for dealing with the issue of fraudulent labeling and adulteration in the global rice industry. In this study, three local varieties of Oryza sativa L. in Vietnam were sequenced with up to ten times genome depth and at least four times coverage (~83%) using the Illumina HiSeq2000™ system, with an average of 6.5 GB clean data per sample, generated after filtering low-quality data. The data was approximately mapped up to 95% to the reference genome IRGSP 1.0. The results obtained from this study will contribute to a wide range of valuable information for further investigation into this germplasm.